2014
DOI: 10.1590/s1806-66902014000100017
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality of sesame seeds during storage

Abstract: -Sesame (Sesamum indicum L.) is one of the oldest oilseed plants used by man, and has great economic potential due to the possibilities for its exploitation in both the domestic and international markets. The objective of this work was to monitor the viability of sesame seeds stored in different environments and packaging, with a view to their conservation. The seeds were packed into paper bags, multiwall paper, black polyethylene and PETE bottles, and stored for a period of 12 months in different environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
(8 reference statements)
4
6
1
2
Order By: Relevance
“…Accordingly, the percent age of metabolically active seeds of P. napostaense decreased while that of dormant and dead seeds increased with increasing age. These results agree with those for other plant species [25][26][27], and are the most likely the result of seed storage conditions [24].…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, the percent age of metabolically active seeds of P. napostaense decreased while that of dormant and dead seeds increased with increasing age. These results agree with those for other plant species [25][26][27], and are the most likely the result of seed storage conditions [24].…”
Section: Discussionsupporting
confidence: 90%
“…The type of packaging materials cannot influence on the moisture content of sesame over storage period (Table 1). Lima et al (2014) demonstrated that the PET bottles packaging applied to laboratory environment and freezer environment show uniform averages with minor variations for water content because the impermeable packing (plastic bottle) is able to isolate the seed from the influence of the external surroundings (air), not allowing moisture exchange with the environment. However, in current experiment, the moisture content was not significantly different among packaging materials, except numerically higher in woven polypropylene bag, it may be due to the relative humidity of natural condition in laboratory which was not high enough to influence the effect of type of packages.…”
Section: Seed Moisture Contentmentioning
confidence: 99%
“…Conditions of low temperature and low relative humidity of the air enable the reduction of the seed respiratory activity and, consequently, the speed of the deterioration process (Carvalho and Nakagawa, 2012;Lima et al, 2014;Smaniotto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%